Students’ Experiences of Modular Learning in Adult Nursing and Adult Nursing Practicum, Bachelor of Nursing Science Program - Promlek, Kesorn; Thasaneesuwan, Samonnan; eesoonthorn, Kanthima; Thongpeth, Wichayaporn (Princess of Naradhiwas University Journal, 2025)
The purpose of this descriptive qualitative study was to explore the experiences of nursing students enrolled in the modular learning of Adult Nursing I and Practicum in Adult Nursing I. Purposive sampling was used to recruit 29 participants who were willing to provide information and had completed these courses during the first semester of the 2022 academic year. Data were collected through focus group discussions in May 2023 and analyzed using content analysis. The study identified five main issues: 1) continuous learning and integrating practical knowledge with theoretical knowledge, 2) learning strategies for success, 3) instructional design supports modular learning, 4) impact of learning on physical and mental health, and 5) managing stress through social support. The findings contribute to a deeper understanding of students’ experiences, learning strategies, and adaptations to achieve modular learning outcomes in Adult Nursing I and Practicum in Adult Nursing I. The findings also highlight both the strengths and areas for improvement in the course design, providing valuable insights for enhancing course structure and teaching and learning approaches to better support students in adapting knowledge to practice. Additionally, learning approaches should be refined to advance the quality of nursing education and improve students’ quality of life.